Pengaruh Lembar Kerja Peserta Didik (LKPD) Berbantuan Video Animasi terhadap Kemampuan Pemecahan Masalah, Motivasi Belajar dan Hasil Belajar Kognitif Peserta Didik - Dian Dwi Lestari; Yusminah Hala; Ismail; Firdaus Daud; Syamsiah (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to determine the effect of animated video-assisted student worksheets (LKPD) on problem-solving skills, learning motivation, and cognitive learning outcomes of eleventh-grade students at SMA Negeri 3 Palu. This study employed a quantitative method with a quasi-experimental design, with a non-equivalent pretest-posttest control group design. The population was all eleventh-grade science students at SMA Negeri 3 Palu, with a sample size of 72 students selected using purposive sampling. Data analysis was conducted using descriptive statistics analysis techniques to describe the effect of animated video-assisted LKPD through pretest and posttest data. Furthermore, inferential statistics analysis was conducted using analysis of covariance to test the research hypotheses. The results of descriptive analysis on each measured variable show that the experimental class taught using animated video-assisted student worksheets achieved higher scores than the control class. This is also proven through significant hypothesis testing on each variable, namely on problem-solving ability (p = 0.03), learning motivation (p < 0.01), and cognitive learning outcomes (p < 0.01). Through the results of this analysis, it can be concluded that animated video-assisted student worksheets have an effective effect in improving students' problem-solving abilities, learning motivation, and cognitive learning outcomes.